Analysis of Nitrogen Sorption Data of Chemically Activated Carbon by the Application of Adsorption Models Based on Surface Coverage and Volume Filling of Micropores. 1. Phosphoric Acid Activated Carbons - M.A. Hourieh; M.N. Alaya; A.M. Youssef; F. El-Sejariah (Adsorption Science & Technology)
Activated carbons were prepared by carbonizing ground apricot stones impregnated with 20–60 wt% phosphoric acid at 300–600°C, in a limited air supply. Highly activated carbons with surface areas amounting to 1200 m 2 /g and pore radii of 8–10 Å were obtained when a mixture of apricot stones and 50 wt% phosphoric acid was carbonized at 450°C. Activation with phosphoric acid proceeds via the creation of pores of radii between 8 Å and 10 Å. The adsorption data for nitrogen at 77 K obey models based on surface coverage satisfactorily and also models based on pore volume filling. Although a slight upward deviation was shown in the Dubinin–Radushkevich (DR) plots, this model was still verified and allowed the determination of useful sorption parameters.